FISHERIES BUSINESS STRATEGY (COLDSTORAGE) IN INCREASING ECONOMIC PROSPERITY AND NEW JOB OPPORTUNITIES IN BANDA ISLAND - Djumadi Djunaidy (Erudio Journal of Educational Innovation, 2021)
This article aims to analyze the role of a cold storage company, namely PT. Harta Samudra, which stands in Nusantara Village, Banda District, in creating job opportunities and improving the economy of the Banda Naira community. Given the current condition of the Bandanese people, they are still vulnerable to the problems of unemployment and scarcity of jobs. The main question of this research is whether the Harta Samudra cold storage has the potential to improve the welfare of the people of Banda Naira, considering the very high productivity of the results obtained by the small fishing industry in Maluku, which can also affect the high economic level of the residents of Banda Naira. This article is based on qualitative research, which takes the subject of corporate employees through observation and interview procedures, heuristic analysis, source criticism, and interpretation. The findings of this research indicate that the Coldstorage Company owned by PT. Samudra's property in Banda Naira has been able to play a role in empowering the people of Banda by opening new jobs and increasing the income of workers who are sufficient for the standard of living of the residents of Banda Naira. Articles can show the positive role of a storage company in Banda, but a case comparison is needed with other similar companies in Banda Naira so that it can become an input for various stakeholders in Maluku and Banda Naira in particular